Spectroscopic behavior of some He peculiar stars - Torres, Andrea Fabiana (2007)
In this work we determine fundamental parameters (Teff and log g) of a sample of He-peculiar stars from the continuum energy distribution around the Balmer discontinuity. Furthermore, we search for optical line variability in some recently discovered objects.